2015
DOI: 10.12659/msm.893442
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Components are Associated with Increased Prostate Cancer Risk

Abstract: BackgroundOur study investigated the associations of metabolic syndrome (MS) and metabolic indicators with prostate cancer (PCa) risk in the Chinese Han ethnic population.Material/MethodsWe studied 101 PCa patients (without/with MS) and 120 healthy controls. Clinical data, including waist circumference, BMI, TG, FINS, FBG, and PCa-related indicators, were collected. The correlations between MS and PCa were analyzed.ResultsCompared to PCa, PV and Gleason scores increased and PSA levels decreased in PCa with MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…As prostate cancer is detected in older men they often also present with co-morbities including obesity, hyperinsulinemia, and insulin resistance. Recent studies have shown an association between metabolic syndrome and an increased risk of prostate cancer progression to advanced disease and prostate cancer-specific mortality [16,17]. A metaanalysis on the association between diabetes and PCa showed that diabetic patients had a reduced risk of developing PCa [18].…”
Section: Prostate Cancermentioning
confidence: 99%
“…As prostate cancer is detected in older men they often also present with co-morbities including obesity, hyperinsulinemia, and insulin resistance. Recent studies have shown an association between metabolic syndrome and an increased risk of prostate cancer progression to advanced disease and prostate cancer-specific mortality [16,17]. A metaanalysis on the association between diabetes and PCa showed that diabetic patients had a reduced risk of developing PCa [18].…”
Section: Prostate Cancermentioning
confidence: 99%
“…In addition to reproductive health, some cases of unhealthy behavior that lead to overweight and obesity can negatively affect men's health and sexual function. For example, studies have shown that a high-fat, high-calorie diet as well as overweight and obesity are associated with erectile dysfunction (11,20,21). At the same time, unhealthy behavior and lack of exploratory health-related behavior are more prevalent in men than in women [22,23]; hence, unhealthy behavior can have more destructive effects on reproductive health in men than in women [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, numerous researchers have demonstrated in clinical, epidemiological, and experimental studies an association of diet and obesity with the development of prostate cancer (Grossmann and Wittert, 2012). Additionally, a meta-analysis study demonstrated that obesity is correlated with an increased risk of aggressive prostate cancer and risk of mortality associated with prostate cancer (Zhang et al, 2015). Additionally, a meta-analysis study demonstrated that obesity is correlated with an increased risk of aggressive prostate cancer and risk of mortality associated with prostate cancer (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with xenographic tumours and transgenic adenocarcinoma mouse prostate (TRAMP) model show that tumour mass and/or volume is increased in mice fed a high-fat diet (Bonorden et al, 2012;Huang et al, 2012;Cho et al, 2015). Additionally, a meta-analysis study demonstrated that obesity is correlated with an increased risk of aggressive prostate cancer and risk of mortality associated with prostate cancer (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%